Radar cross section analysis of various objects and RCS optimisation [Muhtelif cisimlerin radar kesit alani analizleri ve RKA optimizasyonu] - (:unkn) unknown (My University, 2010)
This work is based on the analysis and optimization of the radar cross section that is indispensable for today's defense industry. In this study, radar cross section analysis of many objects from simple geometric structures to military vehicles are made. Nowadays, when the electronic war technology is growing rapidly in, the stealth technology in radar systems became one of the indispensable factors of the defence industry and is used widely in air, land, sea and undersea platforms. Usuage of these techniques that reduces the dedection probability of vehicles that are very important for a country such as ship, plane, helicopter, submarine, etc. is a very important technology in defence industry. On this scope by working on stealth technolgy the methods for reducing radar cross section was investigated detailed.